A bacterially expressed triple-type chimeric vaccine against human papillomavirus types 51, 69, and 26. Issue 42 (6th October 2022) - Yu, Miao; Chi, Xin; Huang, Shiwen; Wang, Zhiping; Chen, Jie; Qian, Ciying; Han, Feng; Cao, Lin; Li, Jinjin; Sun, Hui; Zhou, Lizhi; Li, Tingting; et al.
Abstract: Persistent infection of high-risk human papillomavirus (HPV) is a leading cause of some cancers, including cervical cancer. However, with over 20 carcinogenic HPV types, it is difficult to design a multivalent vaccine that can offer complete protection. Here, we describe the design and optimization of a HPV51/69/26 triple-type chimeric virus-like particle (VLP) for vaccine development. Using E. coli and a serial N-terminal truncation strategy, we created double- and triple-type chimeric VLPs through loop-swapping at equivalent surface loops. The lead candidate, H69-51BC-26FG, conferred similar particulate properties as that of its parental VLPs and comparable immunogenicity against HPV51, −69 and −26. When produced in a GMP-like facility, these H69-51BC-26FG VLPs were verified to have excellent qualities for the development of a multivalent HPV vaccine. This study showcases an amenable way to create a single VLP using type-specific epitope clustering for the design of a triple-type vaccine.